Pharmacist recognition of and adherence to medication-use policies and safety practices - Saad, Aline (2007)
Purpose. Pharmacist recognition of and adherence to medication-use policies and safety practices were assessed. Methods. Simulation testing was used to assess the performance of pharmacists in hypothetical scenarios simulating real-life situations. Fifty test case medication orders were developed, some requiring specific intervention and some requiring no special action. Orders were classified into four categories: those posing safety concerns n ( = 16), those with formulary and product standardization issues (n = 4), those with pharmacy and therapeutics (P&T) committee restrictions (n = 4), and those requiring no special action (n = 26). Potential barriers to compliance were identified by the project team and the orders categorized accordingly. The orders were processed by 25 pharmacists using a simulation testing procedure. Data were analyzed by pharmacists’ demographics, order category, and perceived barriers to compliance. Results. Pharmacists were correctly able to recognize 77.3% of test orders: 67.3% with safety concerns, 98.9% with formulary issues, and 98.5% with restrictions. Appropriate action was taken with 74.2% of test orders: 64.5% of safety orders, 96.6% of formulary orders, and 92.4% of restriction orders. There was no correlation between pharmacists’ performance and demographic characteristics. The two barriers to correct response identified most often were ambiguous responsibility and low perceived level of importance. Conclusion. Pharmacists generally recognized and took appropriate action with simulated medication orders that contained problems related to formulary or P&T committee restrictions. They were less able to recognize and act appropriately on orders with safety-related problems. Ambiguous responsibility and low perceived importance were the most significant factors contributing to noncompliance with P&T committee policies and guidelines.